Analysis of precast segmental box girder bridges - Elmahadi, Mohamed Abdelfatah (2008)
When analyzing prestressed concrete bridges, the self weight, applied loading and prestress have to be combined in the overall structural behavior and the time-dependent effects, such as creep, shrinkage and loss of prestress force should be included. Traditionally these effects are considered separately and then combined with to give the overall design requirements although, in recent years, computer software packages have been developed to combine the effects within a single analysis. The project studies the principles behind structural analysis of the precast segmental box girder bridges. Structural manual analysis was performed in this project to explain the behavior of precast segmental box girder bridges under self-weight of segments unit and prestressing load. Moments due to these loads were computed and compared with the allowable moments that computed using the specifications given in the British code. Analysis of construction stages using this method was conducted using LUSAS (FE computer software). The loads that were taken into account are the self-weight of the cantilever during construction, the prestressig loads, the loss of the prestress, creep,shrinkage and relaxation. The stresses in each construction stage are compared with the specifications given in the British code to ensure that they falls well within acceptable limits.